Oxidative stress in athletes during extreme endurance exercise - Mastaloudis, A.; Leonard, S. W.; Traber, M. G. (Free Radical Biology and Medicine, 2001)
Despite the many known health benefits of exercise, there is a body of evidence suggesting that endurance exercise is associated with oxidative stress. To determine whether extreme endurance exercise induces lipid peroxidation, 11 athletes (3 females, 8 males) were studied during a 50 km ultramarathon (trial 1) and during a sedentary protocol (trial 2) 1 month later. The evening before each trial, with dinner, subjects consumed 75 mg each d(3)-RRR and d(6)-all rac-alpha-tocopheryl acetates. Blood was obtained at baseline, 30 min pre-race, mid-race, post-race, 1 h post-race, 24 h post-race, and at corresponding times during trial 2. All 11 subjects completed the race; average run time was 391 +/- 23 min. Plasma F(2)-isoprostanes increased from 75 +/- 7 pg/ml at pre-race to 131 +/- 17 (p <.02) at post-race, then returned to baseline at 24 h post-race; F(2)-isoprostanes were unchanged during trial 2. Deuterated alpha-tocopherol disappearance rates were faster (2.8 x 10(-4) +/- 0.2 x 10(-4)) during the race compared to the sedentary trial (2.3 x 10(-4) +/- 0.2 x 10(-4); p <.03). These data suggest that extreme endurance exercise results in the generation of lipid peroxidation with a concomitant increase in vitamin E disappearance.